Influence of hydrocolloids in oil-in-water emulsions during storage of food - Lugovska, Oksana; Sidor, Vasyl (My University, 2015)
This paper describes the physico-chemical principles underlying the functional role of hydrocolloids in oil-in-water emulsions. Basic terms such as emulsifier and stabilizer are defined, and the origins of electrostatic and steric interaction potentials are explained. The paper discusses the main factors controlling flocculation, creaming, coalescence and Ostwald ripening, distinguishing between the differing effects of adsorbing and non adsorbing hydrocolloids. The attention is specifically paid to new understanding concerning the rheological and microstructural control of emulsion stability by non-adsorbing hydrocolloids, and the great potential of electrostatic protein-polysaccharide interactions at the oil-water interface to enhance emulsion properties.
Keywords: depletion flocculation; emulsion stability; rheology and microstructure; hydrocolloid emulsifiers; гідроколоїдні емульгатори; виснаження флокуляції; стабільність емульсії; реологічні властивості; мікроструктура; стабильность эмульсии; истощение флокуляции; реологические свойства; микроструктура; гидроколлоидные эмульгаторы; кафедра експертизи харчових продуктів